Development and Validation of Teachers’ Classroom Management Questionnaire (TCMQ) - Asif, Muhammad; Khurram, Azmat Farooq Ahmad; Abdulsattar (Pakistan Journal of Humanities and Social Sciences, 2023)
This research paper aims to outline the development and validation process of the Teachers' Classroom Management Questionnaire (TCMQ), a new psychometric tool designed to measure and evaluate teachers' classroom management skills. The instrument has undergone rigorous testing for its reliability and validity, thus demonstrating its efficacy as an evaluative measure for pedagogical efficacy in classroom management. The preliminary draft of the tool was developed, which consisted of twenty-five (25) items on the five (5) points Likert Scale, which was pilot-tested on three hundred ten (310) public secondary school teachers working in the school education department. Statistical software PLS Smart version 4 was used for the data analysis, validity, reliability, and model fit. CVR of each item was calculated by using the XLStats version 2019. The Teachers' Classroom Management Questionnaire (TCMQ) was developed and validated, exhibiting robust psychometric properties. It may serve as a valuable tool for systematically evaluating classroom management skills in teachers and offers promising avenues for future research and pedagogical interventions. The study findings may help secondary school teachers revisit their classroom management components. This study may open new doors to conduct research for future researchers. The final report elucidates the methodology, findings, and implications for educational research and pedagogical practice. Researchers may use this tool to get data on Classroom Management by using it.